2014
DOI: 10.4103/0301-4738.121141
|View full text |Cite
|
Sign up to set email alerts
|

Etiopathogenesis of cataract: An appraisal

Abstract: Natural eye lens is a crystalline substance to produce a clear passage for light. Cataract is opacity within the clear lens of the eye and is the dominant cause of socio-medical problem i.e., blindness worldwide. The only available treatment of cataract is surgery. However, insufficient surgical facilities in poor and developing countries and post-operative complications inspire researchers to find out other modes of treatment for cataract. In this review, an attempt has been made to appraise various etiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(130 citation statements)
references
References 88 publications
(91 reference statements)
0
91
0
20
Order By: Relevance
“…2,3 Carcinogenesis is similarly related to oxidative stress and oxidative damage. 4 This anti-oxidative insufficiency may occur as a result of faulty anti-oxidative and/or deoxyribonucleic acid (DNA) repair or due to overproduction of reactive oxygen species (ROS) which leads to oxidative damage to cellular macromolecules, genomic instability and uncontrolled cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 Carcinogenesis is similarly related to oxidative stress and oxidative damage. 4 This anti-oxidative insufficiency may occur as a result of faulty anti-oxidative and/or deoxyribonucleic acid (DNA) repair or due to overproduction of reactive oxygen species (ROS) which leads to oxidative damage to cellular macromolecules, genomic instability and uncontrolled cell proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…1 Age related/senile cataract is defined as cataract occurring in people >50 years of age, unrelated to known mechanical, chemical, or radiation trauma. 2 But cataract may present in younger patients referred to as early-onset cataract (EOC). No definitive relationship was reported between cataract and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanism of aspirin mediated protection against cataract formation is not known, however studies have shown that lowering plasma tryptophan levels and reduced aldose reductase activity may be involved [39]. Further, the use of allopurinol suggested that it may be a risk factor for cataract formation [40]. A proposed mechanism for allopurinol reducing the odds of cataract formation is through the inhibition of the antioxidant xanthine oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…nucleus, ER, mitochondria), disturbed cell adhesion or disorganized cytoskeleton. There are specific gene mutations known to cause congenital cataracts (Gupta et al, 2014), such as mutations in the Ephrin receptor tyrosine kinase, EPH receptor A2 (EPHA2), and its ligand Ephrin A5 (EFNA5). Both play a crucial role in lens development and Epha2 or Efna5 knockout mice develop cataracts (Shi et al, 2012;Jun et al, 2009;Cooper et al, 2008).…”
Section: Introductionmentioning
confidence: 99%